Factors associated with exclusive breastfeeding knowledge and practices in a tertiary hospital of Central India - Sahu, Bharti; Thakur, Archana; Gupta, Deepti; Singh, Mrigendra P.; Shrivastava, Ananya; Diwakar, Priyanka; Sabin, Lora L. (International Journal of Contemporary Pediatrics, 2024)
Background: Breastfeeding is a behavioural act of the mother, one that is affected by demographic, socioeconomic, and faith factors as well as by cultural traditions and beliefs. However, there is little scientific literature on potential gaps between knowledge and standard practices regarding exclusive breastfeeding and its predictors among mothers in central India. Methods: A cross sectional study was conducted to explore the knowledge, perceptions, practices, and the associated factors of exclusive breastfeeding among urban and rural mothers at a tertiary hospital of central India. Results: A total of 500 post-natal mothers at the study hospital were interviewed to assess their knowledge and practices of exclusive breastfeeding. The study revealed that knowledge of exclusive breastfeeding was 47% while breastfeeding practices for up to six months of babies was reported by only 15% of participants. Breastfeeding within one hour of birth was reported by 31% of mothers. About 62% did not feed colostrum, while 57% fed their baby pre-lacteal feed. Mothers belonging to a rural community, living in joint family, literate, employed, better-off economic status, multigravida, having a previous history of vaginal delivery, and male child, and those counselled regarding breastfeeding during ANC visits had higher knowledge and better practices of exclusive breastfeeding. Conclusions: The findings of the study suggest an urgent need for regular counselling in ANC clinics to promote exclusive breastfeeding among women and their family caregivers. Breastfeeding awareness education programs for all pregnant women are recommended to ensure that mothers learn best practices regarding breastfeeding and its benefits.